Voices of Janakpurdham: Student Perspectives on Higher Education - Shah, Binod; Tiwari, Uday Kishor; Jha, Brajesh Kumar (Dristikon: A Multidisciplinary Journal, 2024)
Higher education institutions play a crucial role in shaping the socio-economic and cultural landscape of a region. In the context of Janakpurdham, a historically significant city in Nepal, the quality, accessibility, and effectiveness of higher education are vital for the city's progress. This research paper investigates the multifaceted issues and challenges faced by higher education institutions in Janakpurdham and propose strategies for addressing them. Through a comprehensive analysis of data, and literature review, this paper aims to contribute valuable insights to inform policy decisions and enhance the overall higher education landscape in Janakpurdham. This study follows a descriptive and survey research design. The data has been collected by questionnaire method from 160 students of various higher education institutes of different universities. A purposive sampling technique has been used to select respondents. The research findings highlighted the existing disparities in access to higher education, with financial constraints acting as a major barrier. The study revealed diverse perceptions regarding the quality of education and curriculum relevance. The positive feedback regarding alignment with industry demands is encouraging, but efforts must continue to ensure that curriculum evolves to meet changing industry trends and technological advancements. The positive perception of faculty quality and accessibility indicates a solid foundation. The findings of the study can guide policymakers, educators, administrators, and other stakeholders in devising effective strategies to overcome these challenges and enhance the higher education landscape in Janakpurdham.